2019
DOI: 10.1016/j.urology.2018.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Medical Treatments for Hypogonadism do not Significantly Increase the Risk of Deep Vein Thrombosis Over General Population Risk

Abstract: OBJECTIVETo evaluate the risk of deep vein thrombosis (DVT) in men treated with testosterone replacement therapy (TRT) or Clomiphene Citrate (CC) and assess other etiologies for DVT as contributing factors. METHODSRetrospective chart review of 1180 consecutive hypogonadal men who were treated with either TRT or CC. Sixty-four percent had mixed, 16% had primary, and 20% had secondary hypogonadism. RESULTSOf the 1180 men with hypogonadism, 694 were treated with TRT, while 486 were treated with CC. Overall, 10 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Six of the 9 men had other clear provoking VTE risks including lower extremity surgery or trauma, abdominal surgery, or prolonged air travel. 52 In the large U.S. database study of transgender patients previously discussed, the hazard ratio estimates for VTE in all patients in the transmen cohort using testosterone compared with cismen and ciswomen were low at 1.6 (CI, 0.9-2.9) and 1.1 (CI, 0.6-2.1), respectively. 5 Similar results were found in another health claims database case-control study of men with VTE and testosterone use within 15 days of VTE diagnosis during the period from 2007 and 2012, 53 with adjusted OR of 0.9 (95% CI, 0.73-1.12).…”
Section: Vte and Cardiovascular Risks With Hormone Therapy For Ftmmentioning
confidence: 92%
See 2 more Smart Citations
“…Six of the 9 men had other clear provoking VTE risks including lower extremity surgery or trauma, abdominal surgery, or prolonged air travel. 52 In the large U.S. database study of transgender patients previously discussed, the hazard ratio estimates for VTE in all patients in the transmen cohort using testosterone compared with cismen and ciswomen were low at 1.6 (CI, 0.9-2.9) and 1.1 (CI, 0.6-2.1), respectively. 5 Similar results were found in another health claims database case-control study of men with VTE and testosterone use within 15 days of VTE diagnosis during the period from 2007 and 2012, 53 with adjusted OR of 0.9 (95% CI, 0.73-1.12).…”
Section: Vte and Cardiovascular Risks With Hormone Therapy For Ftmmentioning
confidence: 92%
“…In cismen, a recent retrospective study of 694 hypogonadal men treated with testosterone found that only 9 developed VTE with a mean follow‐up of 25 months (+/‐ 21 months). Six of the 9 men had other clear provoking VTE risks including lower extremity surgery or trauma, abdominal surgery, or prolonged air travel . In the large U.S. database study of transgender patients previously discussed, the hazard ratio estimates for VTE in all patients in the transmen cohort using testosterone compared with cismen and ciswomen were low at 1.6 (CI, 0.9‐2.9) and 1.1 (CI, 0.6‐2.1), respectively .…”
Section: Case Iii: Ftmmentioning
confidence: 93%
See 1 more Smart Citation
“…This patient did not subsequently exhibit polycythemia on CC. 51 Recently, Kavoussi et al 52 investigated the risk of deep vein thrombosis (DVT) in 1180 hypogonadal men either on TRT or CC and reported that only 1 out of 486 patients on CC developed DVT compared with 9 out of 694 patients on TRT. In a prospective study of 125 hypogonadal men on CC, Da Ros and Averbeck 49 did not find statistically significant differences when comparing pre-and post-treatment highdensity lipoprotein-cholesterol, triglycerides, fasting plasma glucose, and prolactin levels.…”
Section: Adverse Effectsmentioning
confidence: 99%
“…Other reported, unexpected, and serious complications include branch retinal artery occlusion [17], cerebral infarctions [18], sensorineural hearing loss [19] and high prevalence of obstructive sleep apnoea [20]. However, testosterone therapy has not been associated with an increased risk of deep venous thrombosis [21]. Patients with elevated haematocrit may require therapeutic phlebotomy "venesection" [22] especially if packed cell volume is more than 54% [16].…”
Section: Introductionmentioning
confidence: 99%